Lonely and connected in emerging adulthood: The ambivalence of sociality in a time of transitions - Jeffrey A. Hall; Natalie Pennington; Amanda J. Holmstrom (PLoS ONE, 2025)
Utilizing a large, representative sample of Americans ( N = 4,812), the present manuscript explores individuals’ age in relation to social well-being (i.e., connection, companionship, friendship support, and number of friends) and social ill-being (i.e., loneliness, disconnection). Participants ranged between the ages of 18–95, with a mean age of 43.7. Regression results demonstrate that although social ill-being is higher for emerging adults, social well-being is high for both younger and older adults. Cluster analysis identified four clusters of social ill-being and well-being. Participants in the cluster with high well-being and moderate ill-being were more likely to be young, educated females who had gone through many life changes in the past year. Participants in the cluster with high well-being and lowest ill-being were more likely to be older adults, facing fewer life changes. The present manuscript suggests that loneliness among young adults is not bereft of connection, companionship, and friendship, but instead is characteristic of rapid life changes and a lack of relational permanence and routine.